Química através dos sentidos: texturização de fórmulas para alunos com deficiência visual - Amazonas, Jackline Torres (2014)
That research was accomplished in the attempt of supplying the enormous lack of specific pedagogic resources for the people's learning with visual deficiency that, in the last years, it has been presenting great demand of registrations in different teaching institutions, as it happens annually at the Colégio Pedro II that receives students directed by the Instituto Benjamim Constant for us to enter in the inclusive groups of the medium teaching. Therefore, tends in view the obstacles faced by those students in relation to the understanding of the contents of Chemistry, it was looked for through that research, to develop new pedagogic resources that you/they allow that the students with visual deficiency can have the opportunity to do and to redo the activities how many times are necessary, in a dynamic way, as well as they make the students seers, which not always it is allowed in the specific resources for the visual deficiency. Those materials were introduced to six students with visual deficiency registered in the Unit São Cristóvão III, where during nine encounters they could analyze different textures in the sense of to evaluate which would be the most appropriate material for the making of the same ones. In those encounters the participants acted in the assembly of thirty and a chemical formulas that frequently are approached in the National Exam of the Medium Teaching, tends as base the expressed formulas in symbols acted in the Chemical Orthography Braille for Use in Brazil (MÓL et al., 2011). Starting from then, the results of the research revealed larger tactile sensibility for the pearly plastic texture, with diameter of 0,6 cm, driving the making of two kits, both constituted by pearly pieces in high relief. The first kit was elaborated with eraser material in the black color, with the intention of promoting a larger contrast with the pearly piece in relief, meditating like this, the students with subnormal visual deficiency. While the second kit was elaborated with material of eraser of different shades, seeking to facilitate the use for the teacher for the identification of the classifications of the chemical formulas in Braille. He/she gave way, it was possible to verify that these products assisted in an effective way the students' real needs with visual deficiency, that you/they participated in the research.